Hot shots! ; Hot shots! Part deux [videorecording (DVD)] - Abrahams, Jim, 1944-; Sheen, Charlie; Golino, Valeria; Elwes, Cary, 1962-; Bridges, Lloyd (Twentieth Century Fox Home Entertainment, 2007)
Hot shots!: A team of crack (or is it cracked?) jet jockeys led by an incompetent commander spend their nights carousing and their days training for secret operation "Sleepy Weasel"--A lightning strike against a desert kingdom. Hot shots! Part deux: A do-or-die mission to rescue U.S. hostages in the Mideast takes Topper Harley and his Hot Shots on an action-packed trail booby-trapped with spoofs of movie classics and filled with famous faces in hilarious cameos.